A Model for Provision of ENT Health Care Service at Primary and Secondary Hospital Level in a Developing Country. (3rd September 2013) - Emerson, Lingamdenne Paul; Job, Anand; Abraham, Vinod
Abstract : ENT problems are the most common reason for a visit to a doctor in both rural and urban communities. In many developing countries, there is a lack of ENT specialists and overburdened hospital facilities. To date, there is no comprehensive study that has evaluated the spectrum of ENT disorders in a rural community. Methods . A prospective study was done for a period of three years to profile the cases presenting to the outpatient clinic in a secondary care hospital and in the camps conducted in tribal areas in Vellore District of Tamil Nadu, India. Trained community volunteers were used to identify ENT conditions and refer patients. Results . A total of 2600 patients were evaluated and treated. Otological symptoms were the most commonly reported with allergic rhinitis being the second most commonly reported. Presbycusis was the most common disability reported in the rural community. The other symptoms presented are largely related to hygiene and nutrition. Conclusion . Using trained community workers to spread the message of safe ENT practices, rehabilitation of hearing loss through provision of hearing aids, and the evaluation and surgical management by ENT specialist helped the rural community to access the service.